Kelayakan LKPD dalam pembelajaran daring dan hasil belajar fisika di SMA gorontalo utara - Mohamat Irkan Darise; Masri Kudrat Umar; Tirtawaty Adjul; Raghel Yunginger; Ritin Uloli; Nova Elysia Ntobuo (Educatio, 2022)
Therapping of Student Worksheets (LKPD) has not been carried out optimally, so many practicum activities are not carried out due to limited tools and materials, this affects the results of learning physic is still relatively low. So there is a need for LKPD feasibility research. The purpose of the study was to see the feasibility of the Student Worksheet document (LKPD) on online learning and physics learning outcomes in high school. This type of research is descriptive quantitative, describing the feasibility of LKPD documents and analyzing learning outcomes quantitatively. The research subjects were physics teachers and students totaling 304. Research data were obtained through observations and tests, which were analyzed by percentage scores and analysis of the Rach model. The eligibility data of LKPD documents used by teachers in online learning in three schools are in accordance with the standards set by BSNP reviewed based on aspects of content eligibility, language, presentation, and graphicness, obtaining an overall percentage of 77.08%,78.13% and 74.58% of the good category.  Hasil learned to be analyzed using the Rach model obtained the reliability of items and person items of 0.98 good categories and alpha cronbac 0.47 with sufficient categories, this shows the level of difficulty of the questions is quite good. The use of LKPD in online learning obtained diverse learning outcomes, student learning outcomes at SMAN 1 North Gorontalo with an average score of 65.66 with sufficient categories, SMAN 5 North Gorontalo with an average score of 67.76 with good categories and SMAN 6 North Gorontalo with 61.09 with sufficient categories.